Re-addressing Resilience in Communities Facing the Covid19 Pandemic: An Overview on Coworking Spaces in Central European Peripheries - Danko, Lukáš
Identifikácia toho, akým výzvam čelili coworkingové priestory zo stredoeurópskych krajín počas pandémie Covid-19.